Dynamic familiness capabilities and family business growth: A longitudinal perspective framed within management accounting - Glyptis, Loukas; Hadjielias, Elias; Christofi, Michael; Kvasova, Olga; Vrontis, Demetris (My University, 2021)
This paper examines how dynamic capabilities evolve in relation to familiness resources in order to facilitate family business growth and the way the context underpins dynamic capabilities in the family business. Drawing on an abductive research logic, it explores through a longitudinal in-depth case study and document analysis the way that dynamic capabilities and familiness resources have been deployed by a Greek-owned international shipping company over a twenty-five-year period. The findings highlight the influences exerted by the controlling family on the searching, seizing, and reconfiguring processes within management accounting to enable the reconfiguration of familiness resources in the firm across the dimensions of product strategy, governance, networking and staffing, and financing. These reconfigurations are essential in facilitating company development throughout critical growth junctures. We provide theoretical extensions to the resource-based view (RBV) through an integration of the concept of familiness and dynamic capability view, contextualized theorization, and temporal theorization.
Keywords: Family business; Management accounting; Dynamic capabilities; Familiness; Resource-based view; Strategic resources